(untitled) (Bangladesh Journal of Botany, 2019)
This communication described efficient DNA extraction from Scrophularia and Verbascum samples. Modified Murray and Thompson modified Cota-Sànchez method and Bioflux kit methods were applied for the extraction of DNA. Among the different methods, Bioflux kit Plant DNA extraction kit, coupled with some modification was the best for extraction of high molecular weight DNA as long as the extracted DNA is quantified with fluorescence-based methods.